Neuropathogenesis of Human Rabies - Hanan Farihah, Inas; Dwi Juliardi NR, Akbar; Ananda Audia Arsiazi, Baiq; Nabila, Cahya; Anggrayani, Puput (Jurnal KESANS : Kesehatan dan Sains, 2022)
Rabies is an acute infection that occurs in the central nervous system caused by a virus from the Rhabdoviridae family and the Lyssavirus genus that can be transmitted by dogs, cats, monkeys, bats, civets, and wolves. The purpose of writing this literature review is to determine the definition, epidemiology, neuropathogenesis and the role of neurotransmitters, clinical features, diagnosis, and management of rabies. The method used in writing this journal is a literature review, using literature searching. Search the library using website-based search tools, namely Google and Google Scholar using the keywords Rabies, Human Rabies, and Neuropathogenesis of Human Rabies. Free full text English and Indonesian publications. The journals selected in this literature review are 12 journals published between 2015-2021. Rabies infection begins with the transfer of viral microorganisms into the bite wound through the saliva of an infected animal. Rabies virus receptors consist of nicotinic acetylcholine receptors, Neural cell adhesion molecules (NCAM), and Nerve Growth Factor (NGF). Virus replication occurs in skeletal muscle and spreads via motor or sensory nerves to the spinal cord and brain. The virus binds to the nicotinic acetylcholine receptor via the neuromuscular route. There are 3 neurotransmitters that play a role in the neuropathogenesis of rabies, namely acetylcholine, serotonin, and GABA.